Differences in attitudes of students of Serbian language and students with non-linguistic background towards standard Serbian language (Heritage, 2022)
The aim of this paper is to present students’ attitudes towards standard Serbian language and to find out if results verify the existence of standard language ideologies. In this study there were 240 participants (120 of which were students of University of Belgrade and 120 were students of University of Priština with temporary Head office in Kosovska Mitrovica). Half of that number was students of Serbian language and the other half were students with no linguistic background. The hypothesis we wanted to prove was that students of Serbian language have a more specific perception of standard Serbian language compared to their colleagues that have no formal linguistic education. Students filled in the questionnaire with attitudes they evaluated on a Likert-type scale, and the results were processed statistically. Results prove that students of Serbian language more often categorically agree or disagree with certain claims, that they are more prone to code switching and relating standard language to its traditional areas of use, that they have ideological attitudes towards standard language qualities and negative attitude towards „non-canonical“ linguistic forms, all as a result of higher influence of standard language ideology upon them.
Keywords: language attitudes, language ideologies, standard Serbian language, standard language ideologies, students, students of Serbian language